Integration of solid polymer electrolyte into an efficient and environmentally friendly electrochemical approach in lithium-ion batteries recycling - Mohd Halizan, Muhammad Zharfan; Kasri, Mohamad Arif; Maliaman, Nurul Najiha; Hassim, Awatif; Shafiee, Saiful 'Arifin; Aizamddin, Muhammad Faiz; Shaffee, Siti Nur Amira; Mahat, Mohd Muzamir (Elsevier Ltd, 2025)
The advent of hybrid, plug-in electric vehicle (PHEV), and electric vehicles (EV) into the automotive industry surely to cause the soaring of demand and needs for production of lithium-ion batteries (LIBs) in the nearest future. The lithium element, which is the primary constituent in the LIBs is the most vital component to be available to ensure the circularity and continuity of the LIBs production and application in these technologies and soon, in the next-generation technology such as portable artificial intelligence. Hence, the recycling of the LIBs is basically is the most needed technology advancement through safer and environmentally friendly approach compared to some conventional methods which comprised of chemical and high energy usage such in hydrometallurgy and pyrometallurgy methods. In this work, the electrochemical means to recycle the spent LIBs have been brought forward. In addition, the integration of functional advanced material of solid polymer electrolyte (SPE) has been carried out as the separator membrane to separate the extracted Li-ion from the LIBs black mass and other existing elements in the same black mass. Prior to that, the ample structural, morphological, and electrical studies of the prepared material sample have been carried out to ensure the functionality of the material. The completed set up then was successfully applied for the charging and discharging procedures of the LIBs recycling to be executed. The selectivity for the SPE membrane to permit Li-ion and the precipitate output of the recycling process has been discussed in details in this work. The efficiency of recycling the spent LIBs in this particular work achieved as high as 98 wt%. In addition, the required whole process spans to 70 h including charging and discharging procedures.